2002
DOI: 10.1002/er.783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octane number on exhaust emissions of a spark ignition engine

Abstract: SUMMARYThis paper deals with the experimental study that aims to examine the e!ects of octane number of three di!erent fuel oxygenates on exhaust emissions of a typical spark ignition engine. Three commonly used oxygenates, namely methyl tertiary butyl ether (MTBE), methanol, and ethanol, which were blended with a base unleaded fuel in three ratios (10, 15 and 20 vol%), were investigated. The engine emissions of CO, HC, and NO V were measured under a variety of engine operating conditions using an engine dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
11

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 3 publications
0
13
0
11
Order By: Relevance
“…On the other hand, the effect of RON on detonation has also been studied (Korkmaz, 1996;Bayraktar, 1997;Twu and Coon, 1998;Mogi et al, 1998). Abdulghani (2002) found that as the octane number of the fuel increases the CO and HC emissions decrease but the NO x emission increases.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the effect of RON on detonation has also been studied (Korkmaz, 1996;Bayraktar, 1997;Twu and Coon, 1998;Mogi et al, 1998). Abdulghani (2002) found that as the octane number of the fuel increases the CO and HC emissions decrease but the NO x emission increases.…”
Section: Introductionmentioning
confidence: 96%
“…As seen from the figure, the Mn-based oxides showed significantly lower CO production above 700 C than other oxygen carriers. The ranking of oxygen carriers based on the selectivity of the oxygen carrier towards CO production (moles) at 1000 C was as follows: Mn 3 (1.89). The minimum moles of carbon monoxide produced were 0.03 moles for Mn 3 O 4 at 500 C and maximum moles of carbon monoxide produced were 1.96 moles for CaSO 4 and Na 2 SO 4 at 1200 C.…”
Section: Hydrogen and Co Yieldmentioning
confidence: 99%
“…It was observed that due to the fast oxidation kinetics, the enthalpy of oxidation reaction in air reactor did not show much change for different oxygen carriers with change in temperature. It was seen that the exothermicity of oxidation (kJ) at 1000 C decreased in the following sequence: Mn 3…”
Section: Enthalpy Of Air Reactormentioning
confidence: 99%
See 2 more Smart Citations